2010
DOI: 10.1007/s11805-010-0526-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive factors of early breast cancer

Abstract: OBJECTIVE To identify risk factors for relapse and death in patients with T1 to T2 breast cancer with 0-3 positive axillary lymph nodes. METHODSThe case files of 540 breast cancer patients with T1-T2 tumors with 0-3 positive nodes were reviewed retrospectively. Ten-year locoregional recurrence (LRR), distant recurrence (DR), disease-free survival (DFS) and overall survival (OS) of the patients were analyzed. Univariate statistical analysis and Cox proportional hazards models were carried out with SPSS so ware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The selection of studies was conducted to identify 11 studies related to prognostic factors of recurrence in patients with operable breast cancer in Asia with total sample of 5,213 patients [ 7 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of studies was conducted to identify 11 studies related to prognostic factors of recurrence in patients with operable breast cancer in Asia with total sample of 5,213 patients [ 7 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study in Japan found that HER2 status and axillary metastases are independent predictors of recurrence in breast cancer patients [ 12 ]. In China population, it has been reported that axillary lymph nodal status is the only risk factor of significant impact on 10-year [ 13 ]. In Thailand population, ER + /PR + and HER2 − patients have a higher risk of recurrence in later than 5 years, especially in patients with high ER titer and low nuclear grade.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the use of the indicated markers is widely recommended to define subtypes of BC and to even rank them according to their severity . These differences between tumor subtypes are often associated with clinical features, such as relapse‐free and overall survival and also treatments.…”
Section: Introductionmentioning
confidence: 99%